You care about me, but can I count on you? Applying a psychological contract perspective to investigate what makes employees willing to be internally employable. Issue 9 (14th May 2020) - Solberg, Elizabeth; Lapointe, Émilie; Dysvik, Anders
Abstract: For this study, we adopted a psychological contract-based perspective to investigate whether the fulfillment of perceived developmental promises made to employees is positively related to their willingness to accept internal job-related changes when needed by the organization, a construct we refer to as the willingness to be internally employable . We also examined the role played by line managers in facilitating employees' willingness to be internally employable by fulfilling perceived developmental promises. We tested our conceptual model with data collected from ninety-eight recently hired employees in a Norwegian organization under an initiative emphasizing employee development. We found that developmental promise fulfillment is more important for employees' willingness to be internally employable in this context than any perceived provision of developmental inducements in isolation. Further, we found that employee perceptions of the developmental support provided by their line manager related positively to their willingness to be internally employable by way of developmental promise fulfillment; however, this was not the case with perceived developmental inducements. Our findings support the importance of developmental promise fulfillment in fostering employee willingness to be internally employable and the critical role played by line managers in fulfilling developmental promises that employees believe have been made by their organization.